Linking Parenting and Social Competence in School-Aged Boys and Girls: Differential Socialization, Diathesis-Stress, or Differential Susceptibility? - Spruijt, Andrea M.; Dekker, Marielle C.; Ziermans, Tim B.; Swaab, Hanna (Frontiers in Psychology, 2019)
Girls generally demonstrate superior skill levels in social competence compared to boys. The exact relations of parenting with these gender differences are currently unclear. Gender differences may occur due to exposure to different parenting strategies (differential socialization model) or due to a different impact of similar parenting strategies for boys and girls (differential susceptibility & diathesis-stress model). Objective. In this study we assessed both hypotheses using a multi-method multi-informant approach. We investigated (1) to what extent different parenting strategies mediate the relation between gender and social competence and (2) whether gender and age moderate the relation between parenting strategies and social competence. Design. Parenting strategies were observed during home visits and social competence was assessed using parent and teacher questionnaires and performance-based neurocognitive tasks (N = 98, aged 4 to 8). Results. (1) Parenting strategies did not differ significantly for boys and girls and did not mediate the relation between gender and social competence. (2) Gender moderated the association between parental questioning style and children’s level of social competence: Parents asking fewer questions was associated with poorer social cognitive skills in boys only. Parental supportive presence and intrusiveness were related to aspects of social competence irrespective of gender. Age moderated the relation between parenting and aspects of social competence, though in various (unexpected) directions. Conclusion. Our findings do not support the differential socialization hypothesis and provide partial evidence for a diathesis-stress model as an explanation for parental influence on gender differences in social competence.